Cardiac Specific Overexpression of hHole Attenuates Isoproterenol–Induced Hypertrophic Remodeling through Inhibition of Extracellular Signal-Regulated Kinases (ERKs) Signalling - Xu, W.; Wang, Y.; Zhou, J.; Zhu, X.; Zhang, S.; Yuan, W.; Liu, X.; Shi, Y.; Cao, L.; Zeng, Q.; Jiang, Z.; Ye, X.; et al. (Current Molecular Medicine, 2016)
The human Hole gene (hHole) encodes a six-transmembrane protein with 319- amino acids. Our previous study showed that hHole was strongly expressed in adult heart and may act as a suppressor of extracellular signal-regulated kinases (ERKs), overactivation of which contributed to pathological cardiac hypertrophy. In this study, it was observed that Hole expression was up-regulated in murine hypertrophic hearts. In a cardiac specific transgenic mouse model, it was observed that overexpression of hHole specifically in heart attenuated cardiac hypertrophy and fibrosis induced by isoproterenol (ISO), with blunted transcriptions of ERK1/2, total ERK1/2 proteins and phosphorylated ERK1/2 (p-ERK1/2) levels. Furthermore, overexpression of hHole in mice by hydrodynamic tail-vein injection with hHole plamids also inhibited cardiac hypertrophy induced by ISO. Our work identified hHole as a novel repressor of cardiac hypertrophy, and provided new insights into the possible target for the prevention or treatment of cardiac diseases.
Keywords: isoproterenol (ISO)